Strategi Pemenengan Anggota Legisltaif Perempuan Fraksi Partai Gerindra Pada Pemilu Di Kota Padang Sumatera Barat Tahun 2024 - Wumbu, Yoana Lestonac Elita; Hendrik, Doni (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
In the 2024 Legislative Election, there were 648 legislative candidates, of which 216 were female candidates. However, only 4 female candidates succeeded in securing a seat, one of whom is Dewi Susanti from Padang 4 District representing the Gerindra Party faction. This success highlights the importance of an effective political strategy. This study aims to identify the winning strategies and the supporting factors that contributed to the success of female legislative candidates from the Gerindra Party faction in the 2024 Legislative Election in Padang 4 District. The research uses a qualitative approach with a literature study method, involving data collection from books, literature, notes, and relevant reports. The findings indicate that key factors in Dewi Susanti's victory include the presence of supportive figures behind the candidate, the cohesion of the success team, and financial support for the campaign. Additionally, significant supporting factors in the victory include social, political, and economic capital. This study provides an overview of the importance of combining various strategic factors in achieving victory in legislative elections, particularly for female legislative candidates.